Mobile Phones: Definition, Discourse and Rules of Practice - Lloyd, Clare (Australia and New Zealand Communication Association and La Trobe University, 2007)
This paper reports on a research project which investigates the social and cultural effects of mobile phone use. Examples from my research to date reveal that the communicative practices of mobile phone users are the result of a dynamic mix that is shaping an emerging new discourse; as mobile phones are used in, and are affected by the specific cultural and interpersonal dynamics of contexts. My research examines how mobile phone use is reshaping how we engage with our culture, and considers what discourses feed the meanings we have for mobile phones. This paper illustrates that the use of the mobile phone for interpersonal communication involves a complex negotiation that affects our relationships at home, with the public, with peers, as citizens, and in the workplace.